Occupational stress and its correlates among healthcare workers of a tertiary level teaching hospital in Kathmandu, Nepal, during COVID-19 pandemic: a cross-sectional study - Pranil Man Singh Pradhan; Suchana Thapa (BMJ Public Health)
Background Healthcare workers experience high job stress, contributing to negative health outcomes and poor patient care. This study aims to assess occupational stress and its associated factors among healthcare workers at a tertiary hospital during COVID-19 pandemic in Kathmandu, Nepal.Methods A cross-sectional quantitative study was conducted among doctors and nurses in a tertiary hospital. A self-administered questionnaire was used to collect data from 368 participants. Bivariate and multiple linear regression analysis identified the predictors associated with occupational stress.Results The mean occupational stress index score was 149.56±22.01. It was significantly higher among female participants (151.59±19.12 vs 144.2±27.6, p=0.004), married individuals (152.06±19.79 vs 147.01±23.86, p=0.028), those with over 1 year of employment duration (152.17±21.28 vs 145.45±22.60, p=0.004), health workers attending more than four night shift a month (152.30±19.44 vs 135.52±28.45, p<0.001), those working in rotating shift (151.68±21.12 vs 142.17±23.57, p=0.006), those working 48 hours or more per week (152.39±19.28 vs 145.97±24.66, p=0.005), those lacking support from other staff (157.81±18.70 vs 148.17±22.25, p=0.003) and those who consumed alcohol (152.14±21.25 vs 147.18±22.49, p=0.031). Multiple linear regression revealed associations with employment duration over 1 year (β=0.174, p=0.001), rotating shift (β=−0.106, p=0.006), night shifts (β=0.251, p<0.001), working hours of 48 hours or more per week (β=0.175, p=0.001), lack of support from other staff (β=0.130, p=0.010) and low-wealth quintile (β=0.161, p=0.006).Conclusion Occupational stress is associated with employment duration, night shift, rotating shift, working hours, support mechanisms and socioeconomic profile among healthcare workers. There is a crucial need to establish evidence-based actions to prevent occupational stress and promote the overall health of healthcare workers.